Exploring the Institutionalisation of Science Diplomacy A Comparison of German and Swiss Science and Innovation Centres - Epping, Elisabeth (Kultur und Außenpolitik, 2023)
This work analyses the multi-dimensional concept of science diplomacy. More specifically, it examines the development, establishment and functioning of Science and Innovation Centres (SICs). In an original comparative and longitudinal study, this work closely analyses the institutionalisation of two distinct SICs: Germany's Deutsche Wissenschafts- und Innovationshäuser (DWIH) and Switzerland's Swissnex. It further probes why actors participate in SICs by deciphering their differing rationales and thus developing a distinctly actor-centred perspective on science diplomacy. The findings reaffirm that science diplomacy is clearly driven by national interests, while further highlighting that the notion of science diplomacy and its governance (actors, rationales and instruments) can only be fully understood by analysing the national context in question.